Green Skills in Logistics Vocational Education: A Comparative Study of Curriculum Integration in China and Germany - Pujun Chen (International Journal of Training and Development, 2025)
The logistics sector plays a pivotal role in driving economic growth while addressing environmental sustainability challenges. As the industry transitions towards greener practices, the integration of `green skills' into logistics vocational education and training becomes crucial for equipping the workforce with the competencies needed for sustainable growth. This study explores the integration of green skills into logistics vocational curricula in China and Germany, aiming to gain the current state and challenges in greening the VET curricula for equipping logistics professionals to address the transition towards a green logistics. Using a qualitative curriculum analysis framework inspired by Sterling's model of educational responses to sustainability, this study examines national, regional and school-level curricula to identify the embedded green skills and their integration approaches in both national contexts. The findings reveal both similarities and differences in green skills integration across the two countries. Both contexts exhibit a stronger emphasis on general green skills over logistics-specific and cross-sectoral green skills, reflecting a shared priority for transferable competencies. However, the Chinese curricula demonstrate a fragmented, bottom-up approach with inconsistent alignment between national and school-level curricula. In contrast, the German curricula adopt a more structured, top-down integration strategy, yet inconsistencies at the school level hinder deeper systemic reform. This study concludes that although both countries exhibit evidence of green skills integration, the efforts predominantly remain at the stage of `cosmetic reform'. Greater efforts are needed to strengthen the role of VET in supporting the global green transition, with a particular emphasis on adopting systemic approaches from a transformative perspective to embed sustainability into logistics vocational education.
Keywords: 650; comparative analysis; curriculum integration; green skills; logistics vocational education and training